Anatomical study and distribution of taste buds in the palatal organs of various types of local koi fish (Cyprinus rubrofuscus) in Indonesia - Synthia Regita Noor Mahesti; Aris Haryanto; Krisna Noli Andrian; Tri Wahyu Pangestiningsih (Open Veterinary Journal)
Background: Koi fish (Cyprinus rubrofuscus), celebrated for their vibrant colors and cultural significance, are also valued in the ornamental fish industry. Despite extensive research on fish sensory biology, specific studies on taste buds in koi, especially among different ornamental varieties, are limited.